Small cell sweat gland carcinoma of childhood - Drut, Ricardo (2005)
Small cell sweat gland carcinoma appears to represent a very unusual histological type of sweat gland anlage tumour presenting in children. The differential diagnosis from other small blue cell tumours involving the skin is often difficult. The present report confirms the original observation describing two patients of 2 and 5 years of age harbouring cutaneous tumours. The histology of these lesions showed a monomorphic proliferation of small cells with a high mitotic rate and areas of necrosis. Immunohistochemically, the cells were negative for desmin, cytokeratin 7, cytokeratin 20, Cam 5.2, CD99, chromogranin, CD56, synaptophysin, and S-100, and focally positive for the pancytokeratin marker AE1/AE3, carcinoembryonic antigen (one case), and neurone specific enolase (one case). The prognosis of this type of tumour seems to be good. As more cases are added, the clinical pathological spectrum of the lesion will become better defined.